A cross-sectional study on household's saving behaviour in Malaysia / Faridah Pardi, Azhana Othman and Arifin Md. Salleh - Pardi, Faridah; Othman, Azhana; Md. Salleh, Arifin (2010)
The main objective of this paper is to find the possible relationship between several factors that might have effect on level of savings among households in Malaysia. Previous studies identified number of demographic factors that affect level of savings, such as age of household head, household size number, total consumption, areas of living and level of education. In addition, these studies also applied the lifecycle hypothesis framework that explains the saving behaviour among household. Recent papers investigated whether some of the factors mentioned have significant impact on saving behaviour among household in some countries. They found that not all variables have significant correlation that fits the initial life-cycle framework. The study used the data from the Household Expenditure Survey (HES) obtained from Department of Statistics, Malaysia; as conducted recently in 2004/05. Total number of respondents is 14,084; which 30% from the population allowed to be used. The estimation results show that almost all of the proposed demographic variables have significantly strong positive relationship to the household's level of saving. The finding is consistent with the previous study that demographical factors add huge information in explaining the level of saving. The results also suggest that savings would increase as the rise in age, but declines at a certain point of age, resulted an inverse relationship between age2 and saving. Finally, the analysis results suggest that, by including some other factors, and by taking a bigger sample subset of population might improve the results in future research"JEL classification: E21, 010